Platinum(0)-η2-1,2-(E)ditosylethene Complexes Bearing Phosphine, Isocyanide and N-Heterocyclic Carbene Ligands: Synthesis and Cytotoxicity towards Ovarian and Breast Cancer Cells - Nicola Compagno; Rachele Piccolo; Enrica Bortolamiol; Nicola Demitri; Flavio Rizzolio; Fabiano Visentin; Thomas Scattolin (Molecules, 2024)
A wide range of platinum(0)-η2-(E)-1,2-ditosylethene complexes bearing isocyanide, phosphine and N-heterocyclic carbene ancillary ligands have been prepared with high yields and selectivity. All the novel products underwent thorough characterization using spectroscopic techniques, including NMR and FT-IR analyses. Additionally, for some compounds, the solid-state structures were elucidated through X-ray diffractometry. The synthesized complexes were successively evaluated for their potential as anticancer agents against two ovarian cancer cell lines (A2780 and A2780cis) and one breast cancer cell line (MDA-MB-231). The majority of the compounds displayed promising cytotoxicity within the micromolar range against A2780 and MDA-MB-231 cells, with IC50 values comparable to or even surpassing those of cisplatin. However, only a subset of compounds was cytotoxic against cisplatin-resistant cancer cells (A2780cis). Furthermore, the assessment of antiproliferative activity on MRC-5 normal cells revealed certain compounds to exhibit in vitro selectivity. Notably, complexes 3d, 6a and 6b showed low cytotoxicity towards normal cells (IC50 > 100 µM) while concurrently displaying potent cytotoxicity against cancer cells.